Preparation of Various Salts from Deposits of Egypt - F.R. FOUDA, MOHAMMAD; A. MOUSATAFA, SAMIA (Asian Journal of Chemistry, 2010)
In the present study an investigation of the mineral constituents of evaporates formed in the south- west part of western desert in Egypt has been made. The evaporate samples were analyzed by different techniques. These techniques include chemical analyses, X-ray diffraction patterns and atomic absorption spectra. Simple and application methods were suggested for the preparation of magnesium, aluminium, sodium and potassium salts from these evaporates.